Life expectancy in relation to societal development level: significant discordant factors - Stiperski Matoc, Matea; Stiperski, Zoran; Matoc, Lovro; Valožić, Luka (Central European journal of public health, 2024)
OBJECTIVES: The aim of this study is to determine the interdependence between life expectancy and numerous social indicators, i.e., to determine the factors that encourage an increase or decrease in life expectancy. METHODS: Pearson coefficients as well as linear and logarithmic trends and correlations between the dependent variable of life expectancy and numerous independent variables were calculated and analysed. The calculations were carried out for all countries in the world for which data is available. Based on the strength of the correlations between life expectancy and numerous indicators, we have tried to determine the reasons for the different values of life expectancy in the various countries. RESULTS: Important factors for achieving high life expectancy values are economic development and healthcare spending but the spread of "diseases of the modern era", such as obesity or diabetes, have a significant negative impact on life expectancy. Other important limiting factors for life expectancy are large income inequalities, a higher share of private healthcare expenditure in total healthcare expenditure and lower total healthcare expenditure. Less developed societies can significantly increase their life expectancy by providing clean water and safe sanitation and by combating various infectious diseases (especially HIV). CONCLUSIONS: Life expectancy is a meaningful indicator of the state of social development and accurately reflects the general state of a particular society. It has been shown that GDP per capita (PPP) is a key determinant of life expectancy, while other important factors play the role of a further modifier.
Keywords: Life Expectancy; výdaje na zdravotnictví; Health Expenditures; celosvětové zdraví; mužské pohlaví; ekonomický rozvoj; lidé; Male; Socioeconomic Factors; socioekonomické faktory; Economic Development; ženské pohlaví; Female; Humans; Global Health; naděje dožití